Development and optimization of enteric coated mucoadhesive microspheres of duloxetine hydrochloride using 32 full factorial design - Setia, Anupama; Kansal, Sahil; Goyal, Naveen (International Journal of Pharmaceutical Investigation)
Background: Microspheres constitute an important part of oral drug delivery system by virtue of their small size and efficient carrier capacity. However, the success of these microspheres is limited due to their short residence time at the site of absorption. Objective: The objective of the present study was to formulate and systematically evaluate in vitro performance of enteric coated mucoadhesive microspheres of duloxetine hydrochloride (DLX), an acid labile drug. Materials and Methods: DLX microspheres were prepared by simple emulsification phase separation technique using chitosan as carrier and glutaraldehyde as a cross-linking agent. Microspheres prepared were coated with eudragit L-100 using an oil-in-oil solvent evaporation method. Eudragit L-100was used as enteric coating polymer with the aim to release the drug in small intestine The microspheres prepared were characterized by particle size, entrapment efficiency, swelling index (SI), mucoadhesion time, in vitro drug release and surface morphology. A 32 full factorial design was employed to study the effect of independent variables polymer-to-drug ratio (X1) and stirring speed (X2) on dependent variables, particle size, entrapment efficiency, SI, in vitro mucoadhesion and drug release up to 24 h (t24). Results: Microspheres formed were discrete, spherical and free flowing. The microspheres exhibited good mucoadhesive property and also showed high percentage entrapment efficiency. The microspheres were able to sustain the drug release up to 24 h. Conclusion: Thus, the prepared enteric coated mucoadhesive microspheres may prove to be a potential controlled release formulation of DLX for oral administration.
Keywords: Chitosan; duloxetine hydrochloride; enteric coated microspheres; factorial design; mucoadhesive